PERBANYAKAN BERBAGAI JENIS MIKORIZA ARBUSKULA DI BERBAGAI JENIS TANAMAN INANG - Suntyas Siti Nuridayati; Budi Prasetya; Syahrul Kurniawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The type of mycorrhizae has the behavior of AM colonies on plant roots and different spore formation, so the selection of important host plants in multiplication of AM. This study aimed to test the mycorrhizal propagation and AM colonies in various types of mycorrhiza (Glomus sp. and Acaulospora sp.) in sweet maize, green beans and odot grass, and to study available soil Â P and growth of host plants (sweet maize, green beans and odot grass) inoculated with different types of mycorrhiza (Glomus sp. and Acaulospora sp.). The research included 3 stages of activities, i.e. soil sampling, isolation and identification of mycorrhizae, and propagation of spores. The study used a factorial completely randomized design, consisted of two factors host species (sweet maize, green beans and odot grass) and the types of mycorrhiza (control, Glomus sp. and Acaulospora sp.), totaling 9 treatments and 4 replication of each. The results showed that there were signifance differences in the number of mycorrhizal spores and AM colonies in plant roots (Glomus sp. and Acaulospora sp.). Further, the growth of host plant by aplication of different type of AM was significantly different (P<0,05). Application of mychorriza on plants gave significant effect on available P at 56 days after planting, except in sweet maize.